Sebaran Total Suspended Particulate (Tsp) Dan Particulate Matter 10 (Pm10) Menggunakan Software Aermod Pada Area Sekitar Industri (Studi Kasus: Desa Baruga Kec. Bantimurung Kab. Maros): Distribution Of Total Suspended Particulate (Tsp) And Particulate Matter 10 (Pm10) Using Aermod Software In Areas Surrounding Industrial Areas (Case Study: Baruga Village, Bantimurung District, Maros Regency) - Nur Afifah Shynta Fajriyani Amirullah (JEBE: Journal of Environment Behavior and Engineering, 2025)
Air pollution in today's technological era has reached alarming levels. The cement industry is one of the world's largest contributors to particulate matter. Total Suspended Particulate (TSP) is largely produced by industrial activities, while Particulate Matter 10 (PM10) generally comes from motor vehicle activities. In this study, a descriptive quantitative analysis method was used to determine the distribution of TSP and PM10. The measurement results showed that the lowest particle concentration was found at the PM10 measurement point on holidays, due to reduced vehicle activity. Meanwhile, the distribution patterns of TSP and PM10 were analyzed using AERMOD modeling. The modeling results showed that the closer a location was to the emission source, the higher the concentration of TSP and PM10 pollutants.